If it's not what You are looking for type in the equation solver your own equation and let us solve it.
13/5+(x)=43/5
We move all terms to the left:
13/5+(x)-(43/5)=0
We add all the numbers together, and all the variables
x+13/5-(+43/5)=0
We get rid of parentheses
x+13/5-43/5=0
We multiply all the terms by the denominator
x*5+13-43=0
We add all the numbers together, and all the variables
x*5-30=0
Wy multiply elements
5x-30=0
We move all terms containing x to the left, all other terms to the right
5x=30
x=30/5
x=6
| 5+2/x+5/4x=73/12 | | 5*(x-1)-3*(2x+2)=-1 | | -4x+3÷2x=7÷2x | | 16x+(3-9x)+2x-12=-9 | | 6x=4=45 | | -12+3x+5-9x=29 | | 15,12,7=x2 | | 3x+28+5x+52-10=180 | | R=5n+8 | | 2/3x+1=1/3+3 | | 6x+9-2x-12=-39 | | 6x+9-2x-12=-39- | | 3a+6=-3 | | 13−3s=1 | | 6x+9-2x-12=39- | | 6x+9-2x-12=39 | | 6x+9-2x-12=29 | | 3x+9/4-5x+16/7=0 | | Q=20p-1000 | | x-2/3+x-3/2=x+5/5 | | 7x+42|=28 | | 14x-7=93 | | 5y-20=-8-25y | | 9h=27,h= | | 2(4^2x+2)=76 | | 9/3(6*4/8)=t | | 4(3x+21)=48 | | X+24=4x+21 | | 7x+3=5x+12 | | 8m+7-m=2m-12-5 | | 4a-88=a+17 | | Y+2=-3(x+4) |